2020
DOI: 10.1021/acsabm.0c00390
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Interactions between Acid-/Base-Containing Polymer Nanoparticles and Proteins: Impact of Polymerization pH

Abstract: Electrostatic interaction between synthetic polymer nanoparticles (NPs) and proteins is of considerable importance in the design of NPs that capture, neutralize, and deliver target molecules in a biological milieu. Ionizable functional groups, such as carboxylic acids and amines, are often introduced to NPs to tune the affinity with target bio-macromolecules through electrostatic attraction and repulsion. However, acids/bases are not always ionized at a physiological pH because acidities of the functional grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…AS NDDS possess large cores with a specific surface area, they can interact with various drugs to deliver multiple drugs and realize combination therapy. Furthermore, some nanocarriers have intrinsic functions, such as photothermal conversion, 115 reactive oxygen-generating ability, 116 and neutralizing acid microenvironments, 117 , 118 thus, achieving synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…AS NDDS possess large cores with a specific surface area, they can interact with various drugs to deliver multiple drugs and realize combination therapy. Furthermore, some nanocarriers have intrinsic functions, such as photothermal conversion, 115 reactive oxygen-generating ability, 116 and neutralizing acid microenvironments, 117 , 118 thus, achieving synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noticed that arrangement of the oligomers in NPs is not controlled, and thus the cooperative binding sites for the target are not uniform in this study. The NPs with well controlled arrangement of oligomers would be achieved in the future by using molecular imprinting [8][9][10][11][12][13][14] and/or affinity purification [14][15][16][17] techniques. The use of polymer/molecular support with uniform structure such as uniform polymers [54,55] dendrimers, [51,56,57] precision oligomers [34,40,43,48] and biomacromolecules including peptides, [59] nucleic acids [35,58] and proteins [41,42] and would enable full control of the arrangement of oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] NPs that capture a given target can be prepared by the radical copolymerization of functional monomers that interact with the target molecules. [3][4][5][6][7] Molecular imprinting [8][9][10][11][12][13] and/or affinity purification [14][15][16][17] techniques enable the creation of binding site with strong affinity for the target molecules. It has also been reported that NPs can recognize and neutralize target molecules in the bloodstream of living animals.…”
Section: Introductionmentioning
confidence: 99%
“…Such monomers would be expected to exhibit less tendency to dissociate in the final hydrogel, affecting electrostatically driven protein interactions. NIPAM-based nanoparticles incorporating AAc as an acidic group or N -3-[(dimethylamino)propyl]-methacrylamide (DMAPM) as a basic group exhibited a substantially reduced binding of proteins with complementary charge when polymerized at a pH below or above monomer pKa, respectively [ 113 ]. However, the same hydrogel may exhibit different surface characteristics depending on environmental factors.…”
Section: Hydrogel–biomolecule Interactionsmentioning
confidence: 99%